2021
DOI: 10.1158/0008-5472.can-20-3267
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Modifies Pancreatic Cancer Risk Loci on 2q21.3

Abstract: Germline variation and smoking are independently associated with pancreatic ductal adenocarcinoma (PDAC). We conducted genome-wide smoking interaction analysis of PDAC using genotype data from four previous genome-wide association studies in individuals of European ancestry (7,937 cases and 11,774 controls). Examination of expression quantitative trait loci data from the Genotype-Tissue Expression Project followed by colocalization analysis was conducted to determine whether there was support for common SNP(s)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Indeed, a cross-sectional studies found that ever smoking was associated with higher adherence to Mediterranean diet [41]. An alternative explanation may be the potential interaction between adherence to type 2 diabetes prevention diet and smoking in the etiological pathway to pancreatic cancer, given that smoking has been causally associated with the occurrence of this cancer [42,43]. Importantly, we cannot rule out the possibility that the above difference in the risk of pancreatic cancer between subgroups is a chance finding, though it is mechanistically possible.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a cross-sectional studies found that ever smoking was associated with higher adherence to Mediterranean diet [41]. An alternative explanation may be the potential interaction between adherence to type 2 diabetes prevention diet and smoking in the etiological pathway to pancreatic cancer, given that smoking has been causally associated with the occurrence of this cancer [42,43]. Importantly, we cannot rule out the possibility that the above difference in the risk of pancreatic cancer between subgroups is a chance finding, though it is mechanistically possible.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 458 SNPs of BMI-related genetic variation that simultaneously meet assumptions 1, 2, and 3 were screened from the human genotype–phenotype association database; meanwhile, the SNPs related to smoking ( 26 ) (rs10927006, rs3845344, rs12089815, rs2568958, rs34517439, rs6545714, rs10182416, rs9876664, rs78605811, rs9835772, rs1454687, rs75499503, rs74750282, rs3901286, rs215634, rs12541408, rs7024334, rs11012732, rs6265, rs317656, rs7132908, rs9515446, rs862320, rs9926784, and rs35154326) were deleted. As the aforementioned 25 SNPs were removed, only 433 were retained.…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, smoking accounts for 14% of the population attributed risk (PAR) compared to other risk factors such as alcohol abuse, body mass index, food, and physical exercise [ 14 ]. A genome study of 7937 pancreatic ductal adenocarcinoma (PDAC) cases in 2021 reported a genomic locus that significantly increased PDAC risk with smoking [ 15 ]. Furthermore, multiple studies have proven that smokers are at double the risk for PC compared to non-smokers [ 16 , 17 ].…”
Section: Overview Of Pancreatic Cancermentioning
confidence: 99%